2014
DOI: 10.1002/adma.201305950
|View full text |Cite
|
Sign up to set email alerts
|

A Deformable Nanoplasmonic Membrane Reveals Universal Correlations Between Plasmon Resonance and Surface Enhanced Raman Scattering

Abstract: A quantitative correlation between plasmon resonance and surface enhanced Raman scattering (SERS) signals is revealed by using a novel active plasmonic method, that is, a deformable nanoplasmonic membrane. A single SERS peak has the maximum gain at the corresponding plasmon resonance wavelength, which has the maximum extinction product of an excitation and the corresponding Raman scattering wavelengths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 34 publications
2
48
0
1
Order By: Relevance
“…The decrease of the inter-particle distance from 260 to 220 nm increased the penetration of the electromagnetic field to the Fe 3 O 4 /Au quasi-photonic system and clearly formed large electromagnetic fields (hot spots) around the Au film. As we know, SERS signals linearly increase with the squared product of the local field enhancements at the excitation and Raman scattering wavelengths 23 . The distance between Au nanoparticles in solution substantially affects the field intensity induced by localized surface plasmon resonance (LSPR).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The decrease of the inter-particle distance from 260 to 220 nm increased the penetration of the electromagnetic field to the Fe 3 O 4 /Au quasi-photonic system and clearly formed large electromagnetic fields (hot spots) around the Au film. As we know, SERS signals linearly increase with the squared product of the local field enhancements at the excitation and Raman scattering wavelengths 23 . The distance between Au nanoparticles in solution substantially affects the field intensity induced by localized surface plasmon resonance (LSPR).…”
Section: Resultsmentioning
confidence: 96%
“…It decreases from 263 to 220 nm as the strength of electromagnetic field increases ( Figure 3c ) from 9.5 to 22.2 mT. Note that the inter-particle distance actually affects the electromagnetic (EM) field distribution in the vicinity of a metal surface, which further influences the SERS signal of target molecules 23 . This is why the knowledge of the inter-particle distance of a quasi-photonic crystal is important for practical SERS detection, which will be discussed in the next section.…”
Section: Resultsmentioning
confidence: 98%
“…Recently, it was experimentally revealed that the individual SERS peaks have the maximum enhancement at the maximum products of extinction (absorption) values at the wavelengths of excitation and the corresponding Raman scattering . It is expected that when both of the spectral positions of excitation laser and Raman vibrational modes are located within the perfect absorption broadband of the nanostructures, the intensities of the SERS signals would be dramatically enhanced.…”
Section: Resultsmentioning
confidence: 99%
“…The most popular among this type of approach, involves poly(dimethylsiloxane) (PDMS), an elastomer that is oen used as a supporting substrate due to its transparency, extensibility, and ease of handling. PDMS-based active plasmonic substrates have been widely applied to fundamental research on SPR [32][33][34][35] and surface-enhanced Raman scattering (SERS) 36,37 and applications such as tunable coloring materials. [38][39][40] Although SERS is one of the promising applications for label-free detection of biomolecules such as proteins with high sensitivity by the extreme enhancing effect of Raman scattering signals, which is known as intrinsic chemical ngerprint information, at the enhanced electromagnetic eld on SPR, there are few reports on this, probably due to the unsuitable affinity between PDMS and biomolecules.…”
Section: Introductionmentioning
confidence: 99%